Implementasi Konsep Konektivitas pada Perancangan Interior Surabaya Lettering Community Center - Devi Elvina; Adi Santosa; Poppy Firtatwentyna Nilasari (Intra, 2019)
Interior Design of Surabaya Lettering Community Center is a place of workshop and appreciation for hand lettering lovers, especially for lettering community in Surabaya, known as Subletter. Hand lettering is the art of writing in a beautiful way, which is a trend among the millenials. The purpose of this design is as a place of work art and appreciation of the lettering community, also used as a connector between lettering communities and the people of Surabaya, and other arts communities, both for community recognition, collaboration, and socialization. The vision of this design is to keep the existence of the lettering community in Surabaya, Subletter, to have a positive impact on the environment and social, and to be able to share experiences and educate the public about hand lettering.